THE VALIDATION OF AN ACRYLIC RESIN FOR THE COMPLETION OF BIOMECHANICAL STUDIES ON A MANDIBULAR MODEL - Raluca-Maria Vieriu; Oana Țănculescu; Florentina Mocanu; Alin Aniculăesă; Adrian Doloca; Ionuț Luchian; Silvia Mârțu (Romanian Society of Oral Rehabilitation, 2015)
Aim of the study The aim of this study was to validate the use of a self-curing acrylic resin for the completion of a mandibular model for in vitro studies. Material and methods 25 test specimens were made of acrylic resin (Duracryl Plus, Spofa Dental). The samples were divided in 5 groups, based on monomer to polymer ratio. The determination of the elasticity modulus and of the Poisson's ratio for the studied samples was performed using the electrical resistive tensometry method. The samples were submitted to traction testing on a universal testing machine. Results The elastic characteristics of the material varied significantly depending on the components proportion. The evaluated ratio is 3 parts of powder to 1.5 parts of liquid. This combination presented elastic characteristics similar to those of the spongy bone from the anterior region of the mandible, as well as an average viscosity that contributes to pouring in complex forms, to a proper work time and to a low curing contraction. Conclusions Based on the obtained results, we can consider the use of self-curing acrylic resin, in a ratio of 3:1.5, as being justified for creating a mandibular model to be used in biomechanical tests. Keywords: acrylic resin, strain gauges, mandibular model, modulus of elasticity, Poisson's ratio